Development of the forehand drive instrument in table tennis - Suhermon, Suhermon; Arisman, Arisman; Hendryanto, Ferri; Siska, Siska; Sujae, Ian Harris; Haryanto, Jeki; Indah, Debby; Hamdan, M Nurul; Tofikin, Tofikin (Jurnal Patriot, 2025)
Problems: The problem in this research is that there is no new drive measuring tool in table tennis. Purpose: To make a drive measuring tool for table tennis. Methods: This research method is research and development (R&D). The population and sample in this study were 30 table tennis athletes from PTM Rohul. The study was conducted on May 13, 2025, by administering questionnaires to 2 media experts and 2 material experts. The first drive test was conducted on May 13, 2025, and the second drive test was conducted on May 15, 2025, to test the reliability of this instrument. The criterion test, using a previously existing drive test (from Tomoliyus), was conducted on May 14, 2025, to determine the validity of the test. This study involved samples of 30 PTM Rohul athletes from the first and second tests. The data collection method used questionnaires and tests. Results: The research results obtained from material experts were 87% and 86% (appropriate), and media experts were 85% and 88% (appropriate). Validity was 0.84 and reliability was 0.87. Conclusion: Research on the development of a forehand drive instrument in table tennis has produced a valid and reliable measuring tool to objectively assess the athlete's forehand drive technique. Through stages of content validity, construct validity, and reliability testing, this instrument has been proven to be able to measure aspects of accuracy, speed, and consistency of forehand drive strokes with a high level of accuracy. This study only involved a limited sample from one region or club, so the generalizability of the results still needs to be tested on a wider population. Encourage the development of similar instruments in other table tennis techniques such as backhand drives, chops, and smashes. It is recommended to develop application-based digital instruments, so that forehand drive skill measurements can be carried out efficiently and in real-time